Upaya Peningkatan Kemampuan Berbahasa Anak Melalui Media Visual Pada Anak Kelompok B Tk Desa Karangmojo 01 Kec. Weru Kab. Sukoharjo Tahun Ajaran 2016/2017 - Fitriyanti, Emiya; Dra. Surtikanti, S. H, M. Pd (2017)
ABSTRACT This study aims to determine improvements in language skills of children in group B TK 01 Karangmojo Village district. Weru Kab. Sukoharjo Academic Year 2016/2017 through visual media. This research is a classroom action research (PTK). Subjects in this study were students aged 5-6 group B district. Weru Kab. Sukoharjo academic year 2016/2017. This research was conducted in three cycles in five meetings. The procedure of this study, there are four stages: planning action, action, observation or observation, and analysis and reflection. Data language skills of children and data learning with visual media were collected through observation, interviews, and field notes. This study uses a triangulation method by collecting data from various data sources. Based on the results of cycle I, II, and III that have been conducted, showing improvements in language skills of the students in group B TK 01 Karangmojo Village district. Weru Kab. Sukoharjo Academic Year 2016/2017. Before implementation cycles child who reaches the results obtained evolved according to expectations (BSH) to the top, by 40%, reaching 60% of the first cycle, the second cycle reaches 70%, and the third cycle was 90%. The conclusion from this study that through the visual media can improve language skills of children in group B TK 01 Karangmojo Village district. Weru Kab. Sukoharjo Academic Year 2016/2017. Keywords: language skills of children, visual media